Cost Effectiveness Analysis of Hypertensive Therapy in Hypertensive Patients with Type 2 of Diabetes Mellitus at RSUD Dr. Soehadi Prijonegoro Sragen: Analisis Efektivitas Biaya Terapi Hipertensi pada Pasien Hipertensi dengan Diabetes Melitus Tipe 2 di RSUD dr. Soehadi Prijonegoro Sragen - Jati, Alpian Rona Asmoro; Sugihantoro, Hajar; Syahrir, Ach. (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2025)
Background: Hypertension followed by type 2 diabetes mellitus is a major risk factor for various cardiovascular diseases and is one of the chronic degenerative diseases Hence, it requires long-lasting treatment therapy and high costs. Based on this, hypertensive patients with DM type 2 need special attention in order to get effective hypertensive therapy at minimum cost. Cost-effectiveness analysis is an analytical method for making decisions on the best alternative to the therapy used. Objectives: To determine the most cost-effective hypertensive therapy in hypertensive patients with DM type 2 diabetes who underwent pharmacoeconomic hospitalization with a cost-effectiveness analysis approach. Methods: This type of study is descriptive observational with a retrospective data collection method from January 2021 - June 2023. The data taken was 31 medical records data and bill fees that met the inclusion criteria. Results: The description of drug use in hypertensive patients with DM type 2 diabetes at RSUD Soehadi Prijonegoro Sragen consists of monotherapy (19.35%) and combination (80.65%). The effectiveness of monotherapy was highest in patients receiving amlodipine therapy (12.42 mmHg), while the effectiveness of the combination was highest in patients taking adalat oros + candesartan + bisoprolol + furosemide + clonidine (22,38 mmHg). From the calculation of the ACER value, it was found that the most cost-effective drug was amlodipine, which had an ACER value of Rp. 289,962 in monotherapy and amlodipine + candesartan with an ACER value of Rp. 262,626. Conclusions: The most widely used hypertension therapy is combination therapy; the drug with the highest effectiveness is adalat oros + candesartan + bisoprolol + furosemide + clonidine and the drug with the highest cost-effectiveness is amlodipine monotherapy and the combination of amlodipine + candesartan.